Adsorption of vinazene molecule on graphene layer by computational approach - Siti Najwa Zamri, 1992- author 620830; Rashid Ahmed, 384257; Amiruddin Shaari, supervisor 228360; Fakulti Sains 8004 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Falsafah (Fizik)) - Universiti Teknologi Malaysia, 2017